Comparison of technique characteristics of sprint running at maximal and submaximal speeds - Nemtsev, O.; Nemtseva, N.; Kucherenko, J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to compare the characteristics of athlete's movements when sprint running at maximal and submaximal speeds. Three male and six female sprinters took part in the investigation. Each of them performed 50 metres running: first at 95% of maximal speed, then at maximal speed. High-speed camcorder (240 Hz) was placed at the 40 metres mark of 50 metres track, perpendicular to the plane of athlete`s motion. Paired t-test was used to assess the significance of the differences between considered variables. The study revealed significantly larger ankle vertical velocity along with center of gravity displacement during support phase when sprint running at maximal speed. Step frequency and length, ground contact time and a large number of other variables remained stable during sprint running at various speeds.